Impact of PECS tablet computer app on receptive identification of pictures given a verbal stimulus. (14th August 2013) - Ganz, Jennifer B.; Hong, Ee Rea; Goodwyn, Fara; Kite, Elizabeth; Gilliland, Whitney
Abstract: Objective : The purpose of this brief report was to determine the effect on receptive identification of photos of a tablet computer-based augmentative and alternative communication (AAC) system with voice output. Methods : A multiple baseline single-case experimental design across vocabulary words was implemented. One participant, a preschool-aged boy with autism and little intelligible verbal language, was included in the study. Results : Although a functional relation between the intervention and the dependent variable was not established, the intervention did appear to result in mild improvement for two of the three vocabulary words selected. Conclusion : The authors recommend further investigations of the collateral impacts of AAC on skills other than expressive language.